Dental health, received care, and treatment needs in 11- to 13-year-old children with immigrant background in Heidelberg, Germany - ABDUL-RAZAK BISSAR, CHRYSOULA OIKONOMOU, MARTIN JEAN KOCH & ANDREAS GERHARD SCHULTE (IAPD and Blackwell, 2007)
Over the last two decades, worldwide migration has become a key global issue. The related health issue is taking more importance, and is being increasingly investigated.